Differences between bimodal and unimodal force-time curves during countermovement jump - Peng, H.-T.; Song, C.-Y.; Chen, Z.-R.; Wang, I-L.; Gu, C.-Y.; Wang, L.-I (International Journal of Sports Medicine, 2019)
This study aimed to explore the biomechanical differences between single and double peak ground reaction force-time curves during the countermovement jump with respect to kinematics, kinetics, and coordination of the lower extremities. Twenty-five college students were stratified into a single peak curve group and a double peak curve group. Eight infrared cameras and two force platforms were synchronized to collect the data. Independent t-tests were performed with groups for each dependent kinematic, kinetic and time of the joint extensor concentric contraction variable. Repeated one-way analysis of variance measurements were performed for the time of the ankle, knee and hip extensor concentric contraction in each group. The double peak curve was associated with larger jump height, reactive strength index modified, rate of force development, impulse, hip, knee and ankle flexion, extension angular displacement, and hip and knee moments (p<0.05). The double peak curve group revealed a better hip, knee and ankle (proximal to distal) timing of extensor concentric contractions sequence of the lower extremities during the countermovement jump (p<0.05). The double peak curve group exhibited a more effective countermovement jump movement with respect to biomechanics compared to the single peak curve group.